2014
DOI: 10.1007/s11852-014-0341-0
|View full text |Cite
|
Sign up to set email alerts
|

Public perception and social network analysis for coastal risk management in Maresme Sud (Barcelona, Catalonia)

Abstract: Understanding the governance system, stakeholder relationships and perceptions of coastal landscape risk is essential to improving the sustainability of coastal environments. Our main objective was to analyse social networks for the Maresme Sud coastal area in Catalonia and examine public perceptions of risk in order to shed light on how the current governance system could be improved to promote more adaptive coastal landscape risk management. Our methodology was based on semi-structured interviews of key stak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This research can be understood as an opportunity to solve these problems in a coherent way with the littoral landscape not only in one specific location, but also in other similar places all along the Mediterranean coastline following the methods presented [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Furthermore, in these littoral areas, there is a common conflict between the management of the different implicated administrations [ 22 ] (e.g., municipalities, provinces and government) and also between different infrastructures (e.g., railways, roads and ports). Hence, this research plans to establish unified criteria for the whole littoral that are able to solve most of the detected problematics.…”
Section: Introductionmentioning
confidence: 99%
“…This research can be understood as an opportunity to solve these problems in a coherent way with the littoral landscape not only in one specific location, but also in other similar places all along the Mediterranean coastline following the methods presented [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Furthermore, in these littoral areas, there is a common conflict between the management of the different implicated administrations [ 22 ] (e.g., municipalities, provinces and government) and also between different infrastructures (e.g., railways, roads and ports). Hence, this research plans to establish unified criteria for the whole littoral that are able to solve most of the detected problematics.…”
Section: Introductionmentioning
confidence: 99%
“…This focus on the role of formal stakeholders is key to decision-making power and planning integration especially at the regional and national scale (Fisher, 2017). Governmental actors are more stable and easy to define which contrasts with a previous research on the role of informal relationships of statutory and nonstatutory authorities, where the boundaries and the characteristics of the networks were more diffuse and unstable but resulted relevant at the local level (Roca et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Folke et al (2005) have also shown how social networks can promote accessibility to, circulation and communication of different types of reliable information. Network analysis based on graph theory is a quite a novel approach, yet it seems particularly suited to dealing with power relationships and knowledge distribution in the management of natural resources, as demonstrated by several authors (Berkes et al, 2003;Adger et al, 2005;Bodin and Prell, 2011;Crona and Bodin, 2006;Crona and Parker, 2012;Franquesa and Budapest-Mengual, 2009;Roca et al, 2014). Network structures affect the ability of actors stakeholders to cooperate, share information and adapt their behaviour to new circumstances (Berardo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is observed that "objective" results obtained here reflect a high correlation with stakeholder perceptions for the area ("subjective"). As Roca et al (2015) suggest, stakeholders clearly perceive episodic coastal processes, such as marine storms and flash flooding, as the intensity and frequency of these hazards is regularly reflected in their induced impacts on coastal assets. Thus, Figure 6.4 shows the results obtained for these perceived impacts, where the railway and roads as well as the loss of beach for a protection function, are the items most valued.…”
Section: Erosion and Flooding Risks At The Catalan Coastmentioning
confidence: 99%